PENDAMPINGAN AUDITOR DALAM PENGEMBANGAN KOMPETENSI AUDITOR UNTUK AUDIT PADA BADAN LAYANAN UMUM PEMERINTAH - Respatia, Wimba; Kurnia (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
The development of auditor competency at KAP within the scope of BLU is important to ensure more effective supervision and evaluation of BLU financial performance. Intensive mentoring for auditors at KAP so that they have adequate competence in conducting audits of BLU. The purpose of this community service activity is to improve the competence of auditors in conducting audits at BLU, provide strengthening of the audit process and preparation of training modules. This activity was carried out by providing training and mentoring to auditors at the Public Accounting Firm (KAP) Bambang Sutjipto Ngumar & Rekan in November 2024. The stages of the activity include problem identification, training and mentoring as well as monitoring and evaluation of activities. Participants were given pre-tests and post-tests related to understanding BLU audit procedures. The results of this activity are an increase in auditor competence in BLU financial management, an in-depth understanding of the special audit process at BLU which has unique characteristics compared to other business entities, and a comprehensive guide and training module regarding audits in the BLU division.